K_cam: Hardware/software app to estimate crop coefficients (Kc) through Normalized Difference Vegetation Index (NDVI) using low-cost infra red filter cameras - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
We did field evaluations to determine the sensitivity of the cameras to phenological changes. However, the camera has not yet been calibrated with commercial sensors. There is also an app that is programing to automate the capture of images, processing them and transforming them to Kc and visualize the data.